Early humans (New York : Dorling Kindersley, 2000)
Text and photographs present a description of early humans: their origins; their tools and weapons; how they hunted and foraged for food; and the role of family life, money, religion, and magic.
Keywords: Prehistoric peoples; Civilization, Ancient